Immunohistochemical assessment for Cdx2 expression in the Barrett metaplasia–dysplasia–adenocarcinoma sequence. Issue 2 (23rd November 2010) - Hayes, Stephen; Ahmed, Sajad; Clark, Peter
Abstract : Background: Barrett oesophagus (BO) occurs as a consequence of prolonged gastro-oesophageal reflux and it may precede the development of oesophageal adenocarcinoma. Aims: The aim of this study was to accurately assess Cdx2 expression in the oesophageal metaplasia–dysplasia–adenocarcinoma sequence. Method: The expression of the transcription factor Cdx2 in Barrett metaplasia, high-grade glandular dysplasia and adenocarcinoma was investigated using immunohistochemistry. Results: The results confirmed previous immunohistochemistry and PCR-based investigations, indicating that Cdx2 was expressed by intestinal metaplasia in the oesophagus. In addition, upregulation followed by linear downregulation of Cdx2 expression through the oesophageal metaplasia–dysplasia–adenocarcinoma sequence was demonstrated for the first time. Conclusion: Such downregulation of Cdx2 expression could be in keeping with a role as a tumour suppressor gene, but a simpler explanation would be downregulation of a differentiation marker.